(untitled) (LACCEI, 2024)
The main objective of this research was to know the effect of deductible expenses in the determination of income tax in the general services company BTR R S.A.C., Trujillo 2020 - 2021. The non-quantitative approach was used, with a descriptive level and a non-experimental design. According to the type of research, the interview technique and documentary analysis were used. The results show that in the company there are expenses that exceed the established limit, as well as expense receipts that do not comply with the requirements of the Law on sales receipts. It is concluded that the researcher’s hypothesis is positive because it showed that deductible expenses have a significant effect on the determination of the income tax in the general services company BTR R S.A.C. The research did not present any problems, therefore, there were no limitations.